2005
DOI: 10.1001/jama.293.14.1729
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in the Use of <EMPH>BRCA1/2</EMPH> Testing Among Women With a Family History of Breast or Ovarian Cancer

Abstract: Context Given the current context of racial disparities in health and health care and the historical context of eugenics, racial disparities in the use of genetic susceptibility testing have been widely anticipated. However, to our knowledge there are no published studies examining the magnitude and determinants of racial differences in the use of genetic susceptibility testing. Objectives To investigate the relationship between race and the use of BRCA1/2 counseling among women with a family history of breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
368
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 392 publications
(387 citation statements)
references
References 36 publications
11
368
8
Order By: Relevance
“…This finding is different from studies that have found reduced rates of cancer family history documentation 34 and genetic counseling 35 for nonwhite patients that may underlie the racial disparities observed in uptake of genetic testing for HBOC. 15,36 The number of medical problems was significantly related to documentation of the cancer family history, suggesting that time to discuss family history may have been limited for patients with multiple active medical problems, or clinicians may have perceived collection and documentation of cancer family history as less relevant for these patients.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is different from studies that have found reduced rates of cancer family history documentation 34 and genetic counseling 35 for nonwhite patients that may underlie the racial disparities observed in uptake of genetic testing for HBOC. 15,36 The number of medical problems was significantly related to documentation of the cancer family history, suggesting that time to discuss family history may have been limited for patients with multiple active medical problems, or clinicians may have perceived collection and documentation of cancer family history as less relevant for these patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Available data indicate that African-Americans may be less knowledgeable about genetic testing than non-Hispanic whites and are less likely to have access to genetic services because of lower incomes and limited health insurance coverage . A recent study reported that substantially fewer African American women used genetic testing than white women in a single health care system in a large northeastern U.S. city [Armstrong et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, previous studies systematically document underutilization of risk-appropriate BRCA genetic counseling and testing services among the black community (Chen et al, 2002;Armstrong et al, 2005). One possible explanation lies in lower levels of awareness and knowledge related to HBOC risk and availability of genetic testing services (Hughes et al, 1997;Wideroff et al, 2003b;Simon and Petrucelli, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Given the younger age of onset, a proportion of cases may be due to mutations in the BRCA genes (Chen et al, 2002;Armstrong et al, 2005). However, black women with a family history of breast and/or ovarian cancer are much less likely to access genetic counseling and testing services compared to women from other racial and ethnic groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation